Development Of Student Character Based On Values Of Islamic Religious Education (SCHOOLAR: Social and Literature Study in Education, 2023)
The purpose of this study was to find out the character formation of students at MAN 3 Jombang. As well as what concepts are used in character building, this can be seen from every activity carried out there, starting from entering class, dressing, behaving. The method used in collecting data by way of observation, interviews and documentation using a descriptive qualitative approach. The results of this study indicate that the formation of student character based on the values ​​of Islamic religious education at MAN 3 Jombang has been carrying out character education for a long time through the teachings of the Book of Ta'lim al-Muta'allim which are effective at Islamic boarding schools and at MAN 3 Jombang